Aplicación web para la gestión del proceso de asistencia técnica del proyecto de vinculación con la sociedad de la carrera de Economía de la Universidad Nacional de Loja - Poma Belduma, Jorge Ernesto (2024)
This degree project focuses on the development of a software solution for the management of the technical consultancy process of the project of linking with society of the Economics degree of the Universidad Nacional de Loja, college. For this purpose, a web application was developed through the application of an agile development methodology. The current process of managing the project of linking with society was completely manual, so the students and teachers involved in the project felt the need for a technological tool that would allow them to streamline the tasks and processes specified in the guide format for the development of investment projects, in addition to facilitating the exposition and presentation of the reports of the investment projects to society. In this context, the research question is posed: how can the technical advisory process of the project of linking with society of the Economics degree belonging to the Universidad National de Loja during the period from October 2022 to September 2025 be managed through the use of a web application? To answer this question, the Django framework and the XP development methodology combined with the BPMN technique were used to model the current process. The XP methodology enabled effective, flexible and controlled project management by allowing constant communication and feedback with the client and facilitating the development of unit and acceptance tests. On the other hand, the BPMN technique achieved clear communication with the customer and requirements capture to establish a solid base of shared knowledge. The developed web application offers significant improvements to the existing management process with an intuitive and user-friendly user interface, process automation and an online tracking system. All this increases efficiency and precision in the management of the technical consultancy process. In this way, it was able to respond to the research, offering a practical and effective solution to improve the management of the technical advisory process of the project of linking with society of the Economics degree of the Universidad Nacional de Loja, during the period from October 2022 to September 2025. With this tool, it is expected that participating students and teachers will be able to reduce the time and increase the quality of the products generated, which in turn will facilitate the financing of the projects. Key words: Web application, XP development methodology, BPMN, linkage project.